Ebola and Public Authority: Saving Loved Ones in Sierra Leone. Issue 5 (4th July 2019) - Parker, Melissa; Hanson, Tommy Matthew; Vandi, Ahmed; Babawo, Lawrence Sao; Allen, Tim
ABSTRACT: It is unclear how public authorities shaped responses to Ebola in Sierra Leone. Focusing on one village, we analyze what happened when "staff, stuff, space, and systems" were absent. Mutuality between neighbors, linked to secret societies, necessitated collective care for infected loved ones, irrespective of the risks. Practical learning was quick. Numbers recovering were reported to be higher among people treated in hidden locations, compared to those taken to Ebola Treatment Centres. Our findings challenge positive post-Ebola narratives about international aid and military deployment. A morally appropriate people's science emerged under the radar of external scrutiny, including that of a paramount chief.